Hyperperformer le stéréotype : l’écriture d’une scène de sexe dans The Compleat Purge de Trisha Low - Anne-Lise Solanilla (Genre, Sexualité et Société)
“Vol. II: The sexual assault of Trisha Low as circulated by love in a maze, or, virtue rewarded” is the title of the second part of The Compleat Purge, a poetic text published in 2013 by Trisha Low. It is emblematic of the way in which North-American post-conceptualist poets have seized their conceptualist heritage: they appropriate the words of others in order to reproduce them, to copy them, to pastiche them, in an impure way. In this section, Low evokes, summons, and pastiches different literary genres that formulate female sexuality, and thus say something about the gender identity that is supposed to conform to these practices. Low cites these literary discourses in a way that emphasizes their stereotypical nature, including cliché dialogues and a sex scene written as an adolescent fantasy. This is exactly why Low’s strategy is situated. She is not trying to subvert dominant cultural representations. On the contrary, she is exaggerating them. Her practice performs a form of hyper-identification with the very cultural and aesthetic codes she pastiches. As opposed to aiming at another type of representation separated from the dominant masculine ideology, her strategy aims rather at exaggerating normative scripts – an exaggeration which ends up in exhausting them.